Training child learners on non-native vowel contrasts with phonetic training: the role of task and variability - Brekelmans, G; Evans, B; Wonnacott, E (Wiley, 2024)
Substantial research suggests high variability (multi-talker) phonetic training helps second language adults improve differentiation of challenging non-native speech sounds. Is such training also useful for L2 children? Existing studies have mixed findings and important limitations. We investigate the potential benefits of computerised phonetic training for 50 Dutch 7-year-olds and 39 11-year-olds trained on English vowel contrasts in a two-week study, in a classroom setting. Half received multi-talker, half single-talker input (HV versus LV) with learning evaluated by a battery of tests. Both groups improved in training, however, 11-year-olds improved more. Moreover, 11-year-olds showed generalisation to novel talkers while 7-year-olds did not, with Bayes Factor analyses providing evidence for the null. Generalisation in 11-yearolds was no greater following HV than LV input, with evidence for the null on one of two tasks where generalisation was found. Results are discussed in terms of the interplay between age, task demands and talker variability.